Qualitative vulnerability of the waters of a surface reservoir subjected to drought in a tropical semi-arid region - Castro de Mendonça, Janaina; Bezerra Lopes, Fernando; Maia de Andrade, Eunice; Fernandes Praxedes, Carine; Josivan de Oliveira Lima, Francisco; Helena Oliveira da Silva, Fernanda (Revista Ciência Agronômica, 2023)
Irregular rainfall and the occurrence of droughts in tropical semi-arid regions have a negative impact on the quality and availability of water stored in reservoirs. The aim of this study was to evaluate the quality of water stored in an artifi cial reservoir in the tropical semi-arid region of Brazil during years of drought. The study area was the Pereira de Miranda reservoir, located in the district of Pentecoste, Ceará, Brazil. Seven water-sampling campaigns were carried out between April 2015 and September 2016. The variables to be analysed were chlorophyll-a (Cl-a), hydrogen potential (pH), electrical conductivity (EC), total nitrogen (Ntotal), total phosphorus (Ptotal), transparency (SD), fi xed/volatile/total suspended solids (FSS/VSS/TSS), and temperature (T0 ); the trophic state index (TSI) was then calculated. The variables which better explained the variance in water quality were identifi ed by principal component analysis (PCA). The waters of the Pereira de Miranda reservoir were classifi ed as hyper-eutrophic throughout the study period and at each of the collection points. The PCA identifi ed that the variability in water quality was determined by suspended sediment and nutrients, showing that the reduction in variables made it possible to obtain high explainability of the conditions of the reservoir during monitoring, saving time and resources on the analyses. In addition, the occurrence of severe drought resulted in low accumulated volumes, which intensifi ed and made vulnerable the quality of the waters. As such, the Pereira de Miranda reservoir proved to be in a process of degradation, mainly due to anthropogenic action, intensifi ed by climate factors.